Identification of preferences in decision support systems - Beskorovainyi, V.; Berezovskyi, H. (ECONTECHMOD, 2017)
In this work we obtained the solution of increasing of adequacy of models of multicriteria evaluation for the project and management decision support systems. Modifications of the utility functions of partial criteria and the procedure for calculating their values are proposed, which makes it possible to improve the accuracy of approximation of the preferences of the person making the decision, as well as significantly reduce the time for calculating their values. For the parametric synthesis of universal multicriteria estimation models based on the Kolmogorov-Gabor polynomial, an improvement in the method of comparator identification by calculating the Chebyshev point and the discrepancy vector is proposed.
Keywords: decision support; multi-criteria optimization; utility function of partial criteria